1996
DOI: 10.1111/j.1095-8649.1996.tb00001.x
|View full text |Cite
|
Sign up to set email alerts
|

Diel and seasonal distribution of perch in Lake Constance: a hydroacoustic study and in situ observations

Abstract: A near-shore belt 50 km in length was surveyed parallel to the shoreline or Lake Constancc, central Europe. with a single-beam eehosounder five times between July 1993 and February 1994. The species and age composition or fish in the survey area was investigated by gillnct ti'ihing and SCUBA-diving. In summer. the horizontal distribution of perch was patchy. Population density declined from cast to west. and highest densities occurred in one shallow bay and close to ports and jetties at steeper shores. During … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
1
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 18 publications
5
60
1
1
Order By: Relevance
“…As is known for other fish (Shlaifer 1939;Umezawa et al 1983), the group effect in perch seemed to be induced by visual contact with conspecifics. Field data on the behavior of perch confirm that perch form shoals during twilight and daytime, but during darkness the shoals break up and fish rest on the bottom (Imbrock et al 1996). For ruffe we cannot confirm the need for visual contact for a group effect at a given activity level, because the fish were mostly active during night time.…”
Section: Respiration Rates Of Eurasian Perch and Ruffementioning
confidence: 79%
“…As is known for other fish (Shlaifer 1939;Umezawa et al 1983), the group effect in perch seemed to be induced by visual contact with conspecifics. Field data on the behavior of perch confirm that perch form shoals during twilight and daytime, but during darkness the shoals break up and fish rest on the bottom (Imbrock et al 1996). For ruffe we cannot confirm the need for visual contact for a group effect at a given activity level, because the fish were mostly active during night time.…”
Section: Respiration Rates Of Eurasian Perch and Ruffementioning
confidence: 79%
“…This preference for complex habitats observed throughout the year for the substrate type and to a lesser extent in summer for emerging trees and tree stumps can probably be related to feeding given that they can shelter macro-invertebrates and fish (Czarnecka et al, 2014). With the beginning of autumnal mixing the perch migrated into slightly deeper waters as already described (Craig, 1977;Imbrock et al, 1996). We showed that, in the Bariousses reservoir, the most used and preferred depths shifted to [2.5, 7.5[m in autumn and winter.…”
Section: Seasonal Pattern Of Habitat Use and Preferencementioning
confidence: 78%
“…Considering the advantages of the littoral zone for fish fauna (Schiemer et al, 1995;Schmieder, 2004;Lewin et al, 2014) and the importance of the habitats impacted by WLF for perch (Imbrock et al, 1996;Zamora & Moreno-Amich, 2002;Pekcan-Hekim et al, 2005;Cech et al, 2009;Muska et al, 2013), we expected some changes in the habitat preferences at different WL. As shown on some terrestrial species, variations in habitat availability can lead to changes in habitat preferences (Godvik et al, 2009;Hansen et al, 2009;Pellerin et al, 2010).…”
Section: Influence Of Wl On Habitat Preferencementioning
confidence: 99%
See 1 more Smart Citation
“…For several years, increasing interest has been taken in the study of the spatial distribution of lake fish populations (Bohl 1980, Imbrock et al 1996. In European rivers, some studies have focused on fish microhabitat by taking into account several environmental variables (Nelva et al 1979, Copp 1993.…”
Section: Introductionmentioning
confidence: 99%